The legal environment in the management of healthy lifestyles (Review) (REDEL. Revista Granmense de Desarrollo Local, 2019)
Humanity has always been interested in raising the quality of life and maintaining a good state of physical and mental health. The adoption of healthy behaviors and lifestyles is necessary to achieve that adequate state of health. However, maintaining and managing these behaviors is extremely difficult due to the existence of several factors that influence them. One of the factors that determine lifestyles is the establishment of legality, because there are no human behaviors that are not contemplated, in one way or another, within the legal framework established by the State to conduct society properly. This factor has not always been analyzed and has sometimes been ignored or transgressed by local development interventions that seek to raise the quality of life, which has caused effects contrary to those planned. It is necessary to analyze, from the legal ontology, the environment in which the process of managing healthy lifestyles moves. Based on the distribution of time and activities carried out by people during the day, the analysis of the legal environment is based on the main laws that influence, regulate and make viable the process of managing healthy lifestyles. Among the legal bodies that are analyzed are the Construction and Construction project of the Republic of Cuba (1976), the Labor Code, the Social Security Law, the International Charter of Physical Education, Physical Activity and Sport, among others.
Keywords: management; quality of life; lifestyles; legality; legal ontology; legal environment.